Method for synthesizing diol from glucose

By using a carrier-loaded Pd-WO3 composite nanocatalyst, the catalytic reaction was heated under a hydrogen atmosphere, and the low efficiency and environmental pollution problems of glucose conversion to 1,2-butanediol in the prior art were solved, achieving efficient, stable and economical catalytic effects.

CN119684086APending Publication Date: 2025-03-25FUZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411808357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art synthesis of 1,2-butanediol from glucose has problems such as equipment corrosion, environmental pollution, complex process and high raw material costs, and the yield of directly producing 1,2-butanediol using glucose is relatively low.

Method used

The catalyst was prepared by a carrier-supported Pd-WO3 composite nanocatalyst, and the catalyst was prepared by multi-step impregnation, calcination and hydrogenation reduction method to achieve efficient catalysis of glucose conversion to 1,2-butanediol.

Benefits of technology

Under milder conditions, the efficient conversion of glucose into 1,2-butanediol is achieved, with high catalytic efficiency and conversion rate, stable catalyst activity, reducing production costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179887780000051
    Figure BDA0005179887780000051
  • Figure BDA0005179887780000071
    Figure BDA0005179887780000071
  • Figure BDA0005179887780000072
    Figure BDA0005179887780000072
Patent Text Reader

Abstract

The invention provides a method for synthesizing diol from glucose, which comprises the following steps: adding glucose, a catalyst and deionized water into a reaction kettle, and carrying out heating catalytic reaction in a hydrogen atmosphere to obtain diol, the main product of which is butanediol; wherein the catalyst is a Pd-WO3 composite nano catalyst loaded by a carrier. The catalyst can be used for preparing diol, the novel catalyst is formed by combining the carrier and the specific composite nano-catalyst, the combination can selectively catalyze glucose to be converted into 1, 2-butanediol under mild conditions, and compared with an existing metal catalyst, the catalyst has higher catalytic efficiency and conversion rate; meanwhile, the catalyst is stable in activity and longer in service life, so that the production cost is reduced, and the production efficiency is improved; in addition, the preparation process of the catalyst is simple, the catalyst can keep excellent catalytic activity in the recycling process, and compared with an existing catalyst preparation process, the preparation method has higher production efficiency and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diol preparation, and specifically relates to a method for synthesizing diol from glucose. Background Art

[0002] Diols (ethylene glycol, 1,2-propylene glycol and 1,2-butanediol) are multifunctional and high-value platform chemicals. They are also important intermediates in the chemical industry with a wide range of uses and large market demand. Among them, 1,2-butanediol can be widely used in the polyester industry, such as polyester polyols, polyester resins and polyester plasticizers. In addition, 1,2-butanediol can also be used in the production of organic synthesis (such as an intermediate for the fungicide ethiconazole), moisturizers for cosmetics, pesticides and pharmaceuticals (such as ethambutol, levetiracetam and brivaracetam, etc.).

[0003] At present, the traditional industrial production of 1,2-butanediol is mainly to generate butylene oxide from petroleum-based n-butene through the chlorohydrin method or oxidation method, and then obtain 1,2-butanediol through hydration reaction in the presence of acidic medium. This preparation method has the disadvantages of easy corrosion of equipment, easy pollution of the environment, complex production process route and high cost of raw materials. Therefore, considering the renewability of raw materials, the depletion of fossil fuel resources and the increasingly serious environmental pollution, it is necessary to develop a new, green and sustainable synthetic route for the preparation of diols. Among them, the new approach of using cellulose-based biomass such as glucose to replace traditional petroleum to produce diols has great potential, and this method also has great benefits to the environment and economy. In recent studies, there are few studies on the direct production of 1,2-butanediol using glucose as a raw material, and the yield is low; the main reason is that glucose undergoes a retroacetal reaction to obtain ethanolaldehyde and erythrose; if the alkaline site of erythrose exceeds the hydrogenation active site, its aldehyde group is easy to further undergo a retroacetal reaction to generate C2 compounds, and the yield of butanediol obtained is low. Glucose, as the main component of cellulose, one of the three major components, is of great significance for the high yield of total diols, especially 1,2-butanediol. Summary of the invention

[0004] The object of the present invention is to overcome the defects of the prior art and provide a method for synthesizing glycols from glucose.

[0005] The method of the present invention comprises the steps of:

[0006] Glucose, catalyst and deionized water are added into a reactor, and heated under a hydrogen atmosphere for catalytic reaction to obtain diol, wherein the main product of the diol is 1,2-butanediol; wherein the catalyst is a carrier-supported Pd-WO3 composite nanocatalyst.

[0007] Optionally, the synthesis method of the catalyst is as follows:

[0008] S1: adding a carrier and a tungsten metal salt precursor into water, impregnating and reacting, then heating and drying, and then heating and calcining in air to obtain a carrier-supported WO3 catalyst;

[0009] S2: adding the WO3 catalyst supported by the carrier and the palladium-containing metal salt precursor into water, impregnating the reaction, then heating and drying, and then placing in air for heating and calcining;

[0010] S3: The calcined product is heated and reduced under a hydrogen atmosphere to obtain a carrier-supported Pd-WO3 composite nanocatalyst.

[0011] Optionally, in the catalyst synthesis method, the impregnation reaction time of step S1 is 6 to 20 hours; the heating and drying temperature is 100 to 150° C.; the calcination temperature is 300 to 500° C., and the calcination time is 1 to 5 hours.

[0012] Optionally, in the catalyst synthesis method, the impregnation reaction time of step S2 is 6 to 20 hours; the heating and drying temperature is 100 to 150° C.; the calcination temperature is 300 to 500° C., and the calcination time is 1 to 5 hours.

[0013] Optionally, the hydrogen atmosphere in step S3 of the catalyst synthesis method is 1-10% H2; the heating reduction temperature is 300-500°C, and the reduction time is 5-15h.

[0014] Optionally, the catalytic reaction conditions for obtaining the diol are: a hydrogen atmosphere with a pressure of 4-5 MPa, a temperature of 180-240° C., and a reaction time of 1-10 h.

[0015] Optionally, the mass percentage of the W element in WO3 in the catalyst to the carrier is 5-25wt%; the mass percentage of the Pd in ​​the catalyst to the carrier is 1-3wt%.

[0016] Optionally, the concentration of glucose in water is 0.0025-0.0125 g / mL; the mass ratio of the catalyst to glucose is (0.1-0.5):1.

[0017] Optionally, the metal salt precursors in steps S1 and S3 are ammonium metatungstate and palladium nitrate, respectively.

[0018] Optionally, the carrier is one of TiO2, mesoporous silica, γ-Al2O3, SiO2 and mesoporous molecular sieve.

[0019] More preferably, the carrier is TiO2.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention adopts a carrier and a specific composite nanocatalyst combination to form a new type of catalyst, which is composed of metal Pd and WO3 loaded on the carrier. This combination can selectively catalyze the conversion of glucose into 1,2-butanediol under milder conditions, and has higher catalytic efficiency and conversion rate compared with existing metal catalysts; at the same time, the catalyst activity is stable and has a longer service life, which helps to reduce production costs and improve production efficiency.

[0022] 2. The WO3 oxide and Pd element in the composite nanocatalyst of the present invention, wherein the tungsten oxide mainly provides acidic sites, which play a key role in catalyzing the breaking of CO bonds and CC bonds to adjust the yield distribution, and the metal Pd mainly provides alkaline sites for hydrogenation reactions, which play an important role in the reverse aldol condensation reaction of glucose to generate the target product intermediate. The carrier is preferably TiO2, because the carrier TiO2 provides both acidic sites and alkaline sites, which has a good synergistic effect with this acid-base bifunctional composite nanocatalyst, and can more effectively and selectively catalyze the conversion of glucose into diols, in which the main product is 1-2 butanediol. Therefore, the catalyst and catalytic method of the present invention are particularly suitable for catalyzing the conversion of glucose into diols, and are conducive to the preparation of 1,2-butanediol, obtaining a higher yield, and have a high reference value for the industrial synthesis of 1,2-butanediol.

[0023] 3. The present invention provides a method for preparing a composite nanocatalyst using a multi-step impregnation, calcination and hydrogenation reduction method. The obtained composite nanocatalyst has a nano morphology on the surface of the carrier and is evenly dispersed. The step-by-step synthesis method of Pd and WO3 enables the two to be independently dispersed on the surface of the carrier with small particles, which is beneficial for the two to play a catalytic synergistic function together with a specific carrier.

[0024] 4. The catalyst preparation process of the present invention is simple, easy to operate, and easy to mass produce. Compared with the existing catalyst preparation process, it has higher production efficiency and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Attached Figure 1 is the XRD pattern of the catalyst of Example 9;

[0026] Attached Figure 2 This is the TEM image of the catalyst of Example 9. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0028] Examples 1-15

[0029] As shown in Table 1, 14 different catalyst systems are provided for catalyzing the conversion of glucose into diols. No catalyst is used in Example 1, the catalyst in Example 3 is a commercially purchased catalyst, and the preparation methods of the remaining catalysts are described in detail as follows.

[0030] Preparation method of WO3 catalyst of Example 2:

[0031] The aqueous solution of ammonium metatungstate was placed in an oven, dried at 120°C for 24 hours, cooled to room temperature, fully ground with a mortar and passed through a 100-mesh sieve, and the solid was calcined in a muffle furnace at 400°C for 2 hours.

[0032] Preparation method of xPd / TiO2 catalyst of embodiment 4-6:

[0033] The loading amount x of metal Pd is 1wt%, 2wt% and 3wt% of the mass percentage of Pd in ​​the carrier. It is added to the carrier TiO2 in the aqueous palladium nitrate solution, stirred magnetically for 3 hours to make it evenly mixed, and impregnated for 12 hours. Then the sample is placed in an oven, dried at 120°C for 24 hours, cooled to room temperature, and fully ground with a mortar and passed through a 100-mesh sieve. The solid is calcined in a muffle furnace at 400°C for 2 hours. The calcined solid is reduced in a tubular furnace at 375°C for 10 hours by a volume fraction of 5% H2-95% N2 gas to obtain an xPd / TiO2 sample.

[0034] Preparation method of yWO3 / TiO2 catalyst of Examples 7-9:

[0035] Calculated by the mass percentage of metal element W, the WO3 loading y is 5wt%, 10wt% and 15wt%, added to the carrier TiO2 in the aqueous solution of ammonium metatungstate, magnetically stirred for 3h to make it evenly mixed, and impregnated for 12h. Then the sample was placed in an oven, dried at 120℃ for 24h, cooled to room temperature, and fully ground with a mortar and passed through a 100-mesh sieve. The solid was calcined in a muffle furnace at 400℃ for 2h.

[0036] Preparation method of 2wt% Pd-10wt% WO3 / TiO2 catalyst of Example 10:

[0037] S1: Weigh 0.134g of ammonium metatungstate and dissolve it in deionized water, add it to 0.88g of TiO2 carrier, stir it magnetically for 3h to make it evenly mixed, and soak it for 12h. Then put the sample into an oven, dry it at 120℃ for 24h, cool it to room temperature, grind it thoroughly with a mortar and pass it through a 100 mesh sieve, and calcine the solid at 400℃ in a muffle furnace for 2h to obtain a WO3 / TiO2 sample.

[0038] S2: Add 0.35g of palladium nitrate aqueous solution (the mass fraction of Pd in ​​the aqueous solution is 5%) to the sample WO3 / TiO2, stir magnetically for 3h and continue to immerse for 12h. Then dry and calcine in the same way as S1;

[0039] S3: The calcined solid was reduced in a tube furnace at 375°C for 10 h by using 5% by volume H2-95% by volume N2 gas. The obtained solid was a 2wt% Pd-10wt% WO3 / TiO2 catalyst. The XRD characteristics of the obtained catalyst were as follows: Figure 1 shown.

[0040] like Figure 2 Figures ab show TEM images of the catalyst of Example 9. It can be seen from the figure that the catalyst as a whole is mainly composed of large particles formed by the close accumulation of elliptical or nearly spherical nanoparticles as carrier particles and small particles on the large particles. The large particles are relatively uniform in size, ranging from 30 to 60 nanometers. Figure 2 As shown in Figure c, the lattice fringes of large catalyst particles were measured by high-resolution HRTEM, and the fringe spacing between planes was approximately 0.35 nm and 0.24 nm, which is consistent with the (101) and (004) crystal planes in tetragonal anatase structure TiO2 (PDF#99-0008); and there are some extremely small Pd and WO3 particles distributed on the large particles of TiO2, with extremely fine particle size, which are highly dispersed in the pores of the TiO2 carrier particles. Figure 2 d shows the SAED pattern of the 2wt% Pd-10wt% WO3 / TiO2 catalyst, which has bright electron diffraction rings, which also correspond to the main (101) diffraction peak in TiO2 (PDF#99-0008), indicating that the TiO2 in the catalyst has good crystallinity, and even if metal Pd and WO3 are added, the overall structure of TiO2 crystals is not affected. In addition, Figure 2 As shown in ei, the HAADF-STEM-Mapping image of the catalyst shows some Pd and WO3 nanoparticles with bright spots. Figure 2 ac, it can be seen that the size of Pd and WO3 nanoparticles is as small as 1-10nm, mainly distributed on the surface of TiO2 carrier, and it is observed that each metal (Pd, Ti, W and O) shows a uniform distribution on the catalyst.

[0041] Preparation method of 2wt% Pd-10wt% WO3 / other supported catalysts of Examples 11-15:

[0042] The carrier is changed to pure silicon MCM-41 (mesoporous silicon material), aluminum-containing MCM-41 (mesoporous silicon material), γ-Al2O3, SiO2 and SBA-15 (mesoporous molecular sieve), and the remaining steps and the preparation method of 2wt% Pd-10wt% WO3 / TiO2 catalyst are the same as Example 10.

[0043] The method for preparing butanediol from glucose of embodiment 1-15 is as follows:

[0044] 0.5 g of glucose and 20 mL of deionized water were added to the reactor, and 0.15 g of the catalyst of Examples 1-15 was added respectively. After replacing the air in the reactor with H2 three times, 4 MPa of H2 was filled in, and then the reactor was sealed. Then, the reactor was placed in a heating furnace and reacted for 6 hours at a temperature of 200 ° C and a stirring speed of 600 rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis by liquid chromatography, and the test results shown in Table 1 were obtained. It should be noted that the percentages in Table 1 and other subsequent tables refer to molar percentages.

[0045] Table 1 Test results of Examples 1-15

[0046]

[0047] From the reactions of Examples 1-15 in Table 1, it can be seen that if no catalyst is added during the reaction, as in Example 1, a blank experiment is conducted, and it is found that only a trace amount of ethylene glycol (yield is 0.12%) is produced, and the yield of diol is extremely low. As in Examples 2-3, single metal oxides are used to directly catalyze glucose for reaction, and it is found that WO3 and TiO2 alone as catalysts cannot play a catalytic effect, no 1,2-butanediol is produced, and only a very small amount of ethylene glycol is obtained, which are 0.66% and 0.92% respectively.

[0048] As in Example 4-9, a catalyst of TiO2 loaded with metal Pd or WO3 was used to catalyze glucose to prepare glycol. For the Pd / TiO2 catalyst, when the Pd loading was 1wt%, 2wt% and 3wt%, the total yield of glycol was 21.88%, 18.61% and 13.80%, respectively, and the yield of 1,2-butanediol was 3.59%, 4.98% and 3.71%, respectively. For the WO3 / TiO2 catalyst, when the WO3 loading was 5wt%, 10wt% and 15wt% calculated by the mass percentage of the metal element W, only ethylene glycol was produced, and the yields obtained were 2.43%, 2.52% and 1.58%, respectively.

[0049] As shown in Example 10, the WO3 / TiO2 catalyst was further loaded with Pd, and it was found that the prepared composite nanocatalyst 2wt% Pd-10wt% WO3 / TiO2 had a significant improvement in the preparation of diols from glucose, especially 1,2-butanediol. During the reaction, glucose was completely converted and a total diol yield of 53.28% was obtained, of which the yield of 1,2-butanediol could reach 28.79%, and the yields of ethylene glycol and 1,2-propylene glycol were 5.96% and 18.53%, respectively.

[0050] As shown in Examples 11-15, when the loaded carriers are pure silicon MCM-41, aluminum-containing MCM-41, Al2O3, SBA-15 and SiO2, glucose was not completely converted, and the total yields of glycols obtained were 40.19%, 39.29%, 35.25%, 50.51% and 49.29%, respectively, of which the yields of 1,2-butanediol were 18.87%, 21.15%, 17.76%, 19.75% and 24.23%, respectively, indicating that TiO2, as a catalyst carrier, plays a key auxiliary role in the conversion of glucose and is more conducive to the conversion of glucose into 1,2-butanediol.

[0051] Examples 16-20

[0052] Examples 16-20 show the effect of different WO3 loadings (calculated as the mass percentage of the metal element W, 5-25wt%) of 2wt% Pd Pd-WO3 / TiO2 catalysts on the diol yield. 0.5g of glucose and 20mL of deionized water were added to the reactor, and then 0.15g of the catalyst was added. After replacing the air in the reactor with H2 three times, 4MPa of H2 was filled in, and then the reactor was sealed. Then, the reactor was placed in a heating furnace and reacted for 6h at a temperature of 200°C and a stirring speed of 600rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis.

[0053] It can be seen from Examples 16-20 that when the loading amount of WO3 is 5wt%, the conversion rate of glucose is 100%, and the total yield of diols is 35.78%, of which 1,2-butanediol is 17.65%. As the content of WO3 increases, the yield of 1,2-butanediol also increases continuously. When the loading amount of WO3 is 10wt%, the total yield of diols is 53.28%, and the yield of 1,2-butanediol reaches the highest (28.79%). When the loading amount of WO3 is further increased, it is found that the total yield of diols and the yields of 1,2-propylene glycol and 1,2-butanediol show a trend of increasing first and then decreasing, while the yield of ethylene glycol gradually increases. When the loading amount of WO3 is 20wt%, the total yield of diols can reach 63.73%. It can be seen that when the loading amount of WO3 is 10, 15, 20 and 25wt%, the yield of 1,2-butanediol exceeds the yield of 1,2-propylene glycol and ethylene glycol. Therefore, in order to obtain 1,2-butanediol as the main product, the optimal loading amount (wt%) of WO3 is 5-25wt%, and in particular, when the optimal loading amount (wt%) of WO3 is 10-25wt%, the yield of total glycol exceeds 50%.

[0054] Table 2 Test results of Examples 16-20

[0055]

[0056] Examples 21-25

[0057] Examples 21-25 show the effects of different Pd loadings (1-5wt%) and WO3 loadings of 10wt% on the yield of diols by Pd-WO3 / TiO2 catalysts. 0.5g of glucose and 20mL of deionized water were added to the reactor, followed by 0.15g of catalyst. The air in the reactor was replaced with H2 three times, and then 4MPa of H2 was filled in, and the reactor was sealed. Next, the reactor was placed in a heating furnace and reacted for 6h at a temperature of 200°C and a stirring speed of 600rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis.

[0058] It can be seen from Examples 21-25 that when the Pd loading is 1wt%, glucose is completely converted, and the total yield of diols obtained is 53.06%, of which 1,2-butanediol is 28.07%. The yield of 1,2-butanediol is best (28.79%) when the Pd loading is 2wt%. However, the yield of 1,2-butanediol begins to decrease after the Pd loading continues to increase. When the Pd loading is 5%, the yield of total diols can reach 63.75%. When the Pd loading is 2wt%, the highest 1,2-butanediol yield (28.79%) and a higher total diol yield (53.28%) can be obtained. Therefore, in order to obtain 1,2-butanediol as the main product, the optimal loading amount (wt%) of Pd is 1-3wt%.

[0059] Table 3 Test results of Examples 21-25

[0060]

[0061] Examples 26-34

[0062] Examples 26-34 show the effect of different reaction temperatures (160-250°C) on the yield of diols. 0.5 g of glucose and 20 mL of deionized water were added to the reactor, followed by 0.15 g of 2 wt% Pd-10 wt% WO3 / TiO2 catalyst. After replacing the air in the reactor with H2 three times, 4 MPa of H2 (5% H2 in N2) was filled in, and then the reactor was sealed. Next, the reactor was placed in a heating furnace and reacted for 6 hours at a reaction temperature of 160-250°C and a stirring speed of 600 rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis.

[0063] When the reaction temperature is 160°C, glucose is not completely converted, and the total yield of diols obtained is 47.65%, of which the yield of 1,2-butanediol is 21.73%. When the temperature is raised to 180°C, glucose is completely converted, and the total yield of diols also increases. When the temperature is further raised to 200°C, the total yield of diols is 53.28%, and the yield of 1,2-butanediol can reach the best (28.79%). However, the subsequent temperature rise shows a trend of decreasing the total yield of diols and the yield of 1,2-butanediol. Therefore, based on the catalyst of the present invention, in order to obtain a higher total yield of diols and to have 1,2-butanediol as the main product, the preferred catalytic reaction temperature is 180-240°C.

[0064] Table 4 Test results of Examples 26-34

[0065]

[0066] Examples 35-39

[0067] Examples 35-39 show the effect of different reaction pressures (1-5 MPa) on the yield of butanediol. 0.5 g of glucose and 20 mL of deionized water were added to the reactor, followed by 0.15 g of 2 wt% Pd-10 wt% WO3 / TiO2 catalyst. The air in the reactor was replaced with H2 three times, and then 1-5 MPa of H2 was filled in, and the reactor was sealed. Next, the reactor was placed in a heating furnace and reacted for 6 hours at 200°C and a stirring speed of 600 rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis.

[0068] When the reaction pressure is 1MPa H2, the conversion rate of glucose is 100%, and the total yield of diols is 54.19%, of which 1,2-butanediol is 19.79%. As the reaction pressure increases, the yield of 1,2-butanediol also increases, reaching the highest (28.79%) when the reaction pressure is 4MPa H2, and when the reaction pressure continues to increase to 5MPa H2, the yield of 1,2-butanediol decreases, while the total yield of diols increases. Therefore, based on the catalyst of the present invention, in order to obtain 1,2-butanediol, the preferred catalytic reaction pressure is 4-5MPa.

[0069] Table 5 Test results of Examples 35-39

[0070]

[0071] Examples 40-44

[0072] Examples 40-44 show the effect of different reaction times (1-8h) on the yield of diol. 0.5g of glucose and 20mL of deionized water were added to the reactor, and then 0.15g of 2wt% Pd-10wt% WO3 / TiO2 catalyst was added. After replacing the air in the reactor with H2 three times, 4MPa of H2 was filled in, and then the reactor was sealed. Then, the reactor was placed in a heating furnace and reacted at 200°C and a stirring speed of 600rpm for 1-8h. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis.

[0073] When the reaction time is 1h, glucose can be completely converted, and the total yield of diols and the yield of 1,2-butanediol are 52.96% and 17.22% respectively, while the yield of 1,2-butanediol is not high. After extending the reaction time, the conversion rate of glucose remains stable, and the yield of 1,2-butanediol gradually increases until it reaches the highest at 6h, and the total diol yield reaches 53.28%. After 8h of reaction, the total diol yield and the yield of 1,2-butanediol begin to decline again. It can be seen that the intermediate products or diol products converted from glucose are constantly converted as the reaction proceeds, and are converted into product diols or other non-diol products. Therefore, when the reaction time is 6-8h, it is more conducive to the yield of 1,2-butanediol.

[0074] Table 6 Test results of Examples 40-44

[0075]

[0076]

[0077] Examples 45-50

[0078] Examples 45-50 show the effect of 2wt% Pd-10wt% WO3 / TiO2 catalyst with different number of cycles (1-5 times) on diol yield. 0.5g glucose and 20mL deionized water were added to the reactor, and then 0.15g of 2wt% Pd-10wt% WO3 / TiO2 catalyst was added. After replacing the air in the reactor with H2 three times, 4MPa H2 was filled in, and then the reactor was sealed. Then, the reactor was placed in a heating furnace and reacted for 6h at a temperature of 200°C and a stirring speed of 600rpm. After the reaction was completed, the reactor was cooled to room temperature, the reaction mixture was separated, and the supernatant was taken for product analysis. The catalyst that was circulated in sufficient amount was collected, and then dried in a vacuum drying oven at 65°C for 5h, and directly used for the next reaction after it was dried.

[0079] As shown in Table 7, when the fresh catalyst catalyzes glucose to prepare diols, glucose is completely converted, and the total yield of diols is 53.28%, of which the yield of 1,2-butanediol is 28.79%. When the catalyst is recycled 1, 2, and 5 times, the conversion rate of glucose remains unchanged, and the total yield of diols is 52.54%, 51.45%, and 49.55%, respectively, and the yield of 1,2-butanediol is 27.35%, 26.66%, and 24.07%, respectively. After the catalyst is recycled 5 times, the conversion rate of glucose does not change and remains 100%, the total yield of diols decreases by 3.73%, and the yield of 1,2-butanediol decreases by 4.72%, without significant changes, indicating that the catalyst has excellent stability.

[0080] Table 7 Test results of Examples 45-50

[0081]

[0082] In order to determine the actual content of active components in the fresh 2wt% Pd-10wt% WO3 / TiO2 catalyst and the 2wt% Pd-10wt% WO3 / TiO2 catalyst after being recycled for 5 times, their reaction solutions were subjected to ICP-OES and elemental analysis, as shown in Table 8. ICP-OES showed that the leached content of metal WO3 in the reaction solution gradually increased after the catalyst was recycled for 5 times, and the content of W element increased from 4.31 mg / L to 10.70 mg / L, and metal Pd and Ti were not detected. As shown in Table 9, elemental analysis showed that trace amounts of C and N were generated on the surface of the 2wt% Pd-10wt% WO3 / TiO2 catalyst after the catalyst was recycled for 5 times. ICP-OES and elemental analysis once again showed that the catalyst had excellent stability.

[0083] Table 8 Detection results of metal elements in the reaction solution

[0084]

[0085] Table 9 Detection results of C, N and S elements on the catalyst surface

[0086]

[0087] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for synthesizing glycols from glucose, characterized in that: Glucose, catalyst and deionized water are added into a reactor, and heated under a hydrogen atmosphere for catalytic reaction to obtain diol, wherein the main product of the diol is 1,2-butanediol; wherein the catalyst is a carrier-supported Pd-WO3 composite nanocatalyst.

2. The method for synthesizing butanediol from glucose according to claim 1, characterized in that: The synthetic method of the catalyst is as follows: S1: adding a carrier and a tungsten metal salt precursor into water, impregnating and reacting, then heating and drying, and then heating and calcining in air to obtain a carrier-supported WO3 catalyst; S2: adding the WO3 catalyst supported by the carrier and the palladium-containing metal salt precursor into water, impregnating and reacting, then heating and drying, and then placing in air for heating and calcining; S3: The calcined product is heated and reduced under a hydrogen atmosphere to obtain a carrier-supported Pd-WO3 composite nanocatalyst.

3. The method for synthesizing butanediol from glucose according to claim 2, characterized in that: In the synthesis method of the catalyst, the impregnation reaction time of step S1 is 6 to 20 hours, the heating and drying temperature is 100 to 150° C., the calcination temperature is 300 to 500° C., and the calcination time is 1 to 5 hours; the impregnation reaction time of step S2 in the synthesis method of the catalyst is 6 to 20 hours, the heating and drying temperature is 100 to 150° C., the calcination temperature is 300 to 500° C., and the calcination time is 1 to 5 hours.

4. The method for synthesizing butanediol from glucose according to claim 2, characterized in that: The hydrogen atmosphere in step S3 of the catalyst synthesis method is 1-10% H2; the heating reduction temperature is 300-500°C, and the reduction time is 5-15h.

5. The method for synthesizing butanediol from glucose according to claim 2, characterized in that: The metal salt precursors in step S1 and step S2 are ammonium metatungstate and palladium nitrate, respectively.

6. The method for synthesizing butanediol from glucose according to claim 1, characterized in that: The catalytic reaction conditions for obtaining butanediol are: a hydrogen atmosphere with a pressure of 4-5 MPa, a temperature of 180-240° C., and a reaction time of 6 to 8 hours.

7. The method for synthesizing butanediol from glucose according to claim 1, characterized in that: The concentration of the glucose in water is 0.0025-0.0125 g / mL; the mass ratio of the catalyst to the glucose is (0.1-0.5):

1.

8. The method for synthesizing butanediol from glucose according to claim 1, characterized in that : The mass percentage of W element in WO3 in the catalyst to the carrier is 5-25wt%; the mass percentage of Pd in ​​the catalyst to the carrier is 1-3wt%.

9. The method for synthesizing butanediol from glucose as claimed in claim 1, wherein: The carrier is one of TiO2, mesoporous silicon, γ-Al2O3, SiO2 and mesoporous molecular sieve.

10. The method for synthesizing butanediol from glucose according to claim 1, characterized in that The catalyst carrier is TiO 2。

Citation Information

Cited By

  • Zn-Pd bimetal hierarchical pore ZSM-5 molecular sieve and preparation method and application thereof

    CN120861136A